Le sens des référentiels professionnels et les processus de signification et de référence - Christian Bélisson (Université de Provence, 2017)
Through the analysis of "frames of reference", the article asks the question of the sense/meaning of professional practices. The notion of "sense/meaning" is defined as the product of processes of signification and reference. The paper proposes a brief explanation of these processes, based on the work of linguistics, semiology and pragmatics. The empirical part illustrates these remarks with an analysis of a brief statement and the synthesis of the results of two experiments. The problem of the differentiation between the universe of the symbolic and that of the conceptions is thus approached through the social representations that are constructed in socio-professional circles. Professional practices are therefore repositioned in the context of the technicization of postmodern society, the expansion of the division of labor and the conceptual enrichment of our culture.